Variable-parameter double-power reaching law sliding mode control method. (2nd July 2020) - Kang, Zhongjian; Yu, Hongguo; Li, Changchao
Abstract : To solve the problem of the slow convergence rate of the reaching law and the chattering problems in the dynamic response in the sliding mode control, an improved double-power sliding mode reaching law is proposed. The reaching law is adjusted by changing the magnitude of the power terms adaptively at different stages of the system approach process, and the convergence speed of the dynamic response process is greatly improved. Its existence, accessibility and stability are proven by theory. The simulation results show that the improved double-power reaching law is faster than the double-power reaching law and the fast power reaching law. When there is uncertainty in the system, the system state and its derivatives can rapidly converge to the neighbor-hood of the equilibrium zeros. In the presence of time-varying perturbations of the two-order system, the sliding mode control system based on the improved double-power sliding mode reaching law has higher tracking precision of the given signal and differential signal and effectively reduces the high-frequency chattering phenomenon of the control input signal.